Upaya Peningkatan Motivasi Belajar Siswa Menggunakan Media Wordwall dan Metode Pembelajaran Kontekstual - Yuningsi, Nurasmi; Korompot, Chairil Anwar; Hasniar, Hasniar (Indonesian Journal of Pedagogical and Social Sciences, 2023)
Abstract. This study aimed to determine the increase of motivation in subjects Past Tense and Perfect Tense for XI TKJ II students of Vocational High School 4 Jeneponto. This research is classroom action research (PTK) and the subjects were students of class XI TKJ Vocational High School 4 Jeneponto, amounting to 32 students. In contrast, the object is students’ motivation in learning. Data on students’ motivation in learning was collected through observations, questionnaires, tests, documentation, and interviews. The data analysis in this study applied descriptive data analysis. Based on the research that has been done, it can be concluded that the application of the Wordwall media and contextual teaching method can increase students' motivation and learning outcomes on subjects Past Tense and Perfect Tense of XI TKI II students of vocational high school four Jeneponto. Keywords: Motivation, Wordwall, Method, Contextual